Страстите во сферата на даденото и зададеното кај Аристотел и кај свети Максим Исповедник - Nedeski, Viktor (Филозофски факултет Скопје, 2020)
In this paper, the views of Aristotle and Saint Maximus the Confessor on the passions of the soul in the sphere of the Logos and Tropos in man are considered comparatively. First, the study of the passions of each of them is studied separately, and the essence of their approach is isolated from the extensive material of their anthropological gnoseology. Then, it is examined which segments of both views overlap or diverge. Finally, the gap which is dividing the ancient and church perspective and the perception of passions in the sphere of the Logos and Tropos is determined.
Keywords: Aristotle, St. Maximus the Confessor, passions, logos, tropos, given, assigned